2015
DOI: 10.1002/cjce.22158
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of transesterification reaction using CAO/AL2O3 catalyst synthesized by sol‐gel method

Abstract: Calcium oxide is one of the appropriate catalysts for biodiesel production. In this study, 40 wt. % CaO/Al 2 O 3 catalyst was used. Transesterification reaction was performed in optimal condition presented in the previous study (0.05 molar nitric acid and gelation temperature of 70 8C) in a 250 mL two-necked flask. All the experiments were carried out in the presence of soybean oil, methanol (methanol to oil molar ratio of 12:1), and catalyst concentration of 6 wt. %. Stirrer speed was set at 350 rpm. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…. Dosunmu and Shah [19] Statistical % deviation 9.55 % 10 % Moradi et al [14] Statistical R 2 0.9622 0.96 Bustillo-Lecompte et al [20] Statistical Mean 1628 mg · L −1 1600 mg · L −1 Abdelaziz et al [6] Statistical Standard deviation ±4.31*10 −5 M ±0.04 × 10 −3 mol/L (or 40 mol/L) Verma et al [13] Statistical F value 369.5 370 this value depend on sampling procedures, instrument characteristics, calibration, and environmental conditions, all of which reduce the precision of the data.…”
Section: Analytical Datamentioning
confidence: 97%
See 1 more Smart Citation
“…. Dosunmu and Shah [19] Statistical % deviation 9.55 % 10 % Moradi et al [14] Statistical R 2 0.9622 0.96 Bustillo-Lecompte et al [20] Statistical Mean 1628 mg · L −1 1600 mg · L −1 Abdelaziz et al [6] Statistical Standard deviation ±4.31*10 −5 M ±0.04 × 10 −3 mol/L (or 40 mol/L) Verma et al [13] Statistical F value 369.5 370 this value depend on sampling procedures, instrument characteristics, calibration, and environmental conditions, all of which reduce the precision of the data.…”
Section: Analytical Datamentioning
confidence: 97%
“…Factors that influence Guedes et al [3] Pure Temperature 315.71827 K 315.7 K Lu et al [4] Pure Pressure 101 325 Pa 101 kPa Kianinejad et al [5] Pure Porosity 52.47 % 52 % Abdelaziz et al [6] Pure Length 2.655 m 2.65 m Jeon et al [7] Analytical Surface area 163.9 m 2 · g −1 160 m 2 · g −1 Lin et al [8] Analytical EDS analysis 40.09 wt% 0.40 g · g −1 Jia et al [9] Analytical Viscosity 5.875 cP 5.9 cP Ma et al [10] Derived Selectivity 63.3 63 Vedoy and Soares [11] Derived Solids recovered 25.97 % 26 % Esmailpour et al [12] Derived Air density 0.921 02 kg · m −3 0.92 kg · m −3 Verma et al [13] Derived COD 1000.00 mg · L 1 .00 g · L Moradi et al [14] Derived Activation energy 36.314 kJ · mol…”
Section: Analytical Datamentioning
confidence: 98%
“…[22] Various important studies have been reported in the case of thermodynamics and kinetics for reaction mixture of organic carbonates and liquid phase reactions. [23][24][25][26][27][28] However, no study of thermodynamics has been performed comparing various routes for DEC synthesis. Considering this, a comprehensive effort was carried out for estimation of equilibrium constants at standard temperature and pressure.…”
Section: Iethyl Carbonate (Dec)mentioning
confidence: 99%
“…Various important studies have been reported in the case of thermodynamics and kinetics for reaction mixture of organic carbonates and liquid phase reactions . However, no study of thermodynamics has been performed comparing various routes for DEC synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous solid acid catalysts are superior over homogenous catalysts owing to their numerous advantages such as no equipment corrosion and easy separation from product mixture . Tin (IV) compounds were employed to catalyze the hydrolysis of triacylglycerides .…”
Section: Introductionmentioning
confidence: 99%